Testing the Convergence Hypothesis - Lichtenberg, Frank R. (The Review of Economics and Statistics, 1994)
The authors show that, contrary to the beliefs of some previous analysts of international economic growth, the hypotheses of convergence and of mean-reversion are not equivalent. Under some assumptions, the rate of convergence is independent of the degree of mean-reversion; under other assumptions, mean-reversion is a necessary, but not a sufficient, condition for convergence. The authors show the relationship between the convergence test and the mean-reversion test and provide an empirical example in which the null hypothesis of no mean-reversion is rejected but the null hypothesis of no convergence is not rejected. Copyright 1994 by MIT Press.